Improving indoor air quality and occupant health through smart control of windows and portable air purifiers in residential buildings. (September 2022) - Wang, Yan; Cooper, Elizabeth; Tahmasebi, Farhang; Taylor, Jonathon; Stamp, Samuel; Symonds, Phil; Burman, Esfandiar; Mumovic, Dejan
Indoor exposure to PM2.5 (particulate matter with aerodynamic diameter less than 2.5 μm) has a substantial negative impact on people's health. However, indoor PM2.5 can be controlled through effective ventilation and filtration. This study aimed to develop a smart control framework that (1) combines a portable home air purifier (HAP) and window control system to reduce indoor PM2.5 concentrations whilst maintaining thermal comfort; (2) evaluates the associated health impacts and additional energy use. The proposed framework was demonstrated through a simulation-based case study of a low-energy apartment. The simulation results showed that joint control of HAP and window openings has great potential to not only maintain thermal comfort but also achieve effective PM2.5 removal which, consequently, can lead to considerable health benefits at a low additional energy cost. Compared to similar previous studies, the strength of the proposed control framework lies in combining window operations and HAPs in the same system and including both thermal comfort and indoor PM2.5 as the control targets. This work also introduces a novel concept of linking a building control system with a health impact assessment, an important and innovative step in the creation of holistic and responsive building controls. Practical application: This study proposes a novel control framework that jointly controls portable home air purifiers (HAPs) and windows to maintain thermal comfort and achieve effective PM2.5 removal. The simulation results suggest that such a hybrid control strategy can result in considerable health benefits at low additional energy costs.